Handbook of research on modern optimization algorithms and applications in engineering and economics - Vasant, Pandian 1961-; Weber, Gerhard-Wilhelm 1960-; Vo Ngoc Dieu 1971- (Advances in Computational Intelligence and Robotics (ACIR) Book Series, 2016)
"This book highlights the latest research innovations and applications of algorithms designed for optimization applications within the fields of engineering, IT, and economics, focusing on a variety of methods and systems as well as practical examples"...